Answering the Challenges of Polygamy: Justice and Legal Protection in Islamic and Indonesian Law - Yenny Febrianty; Hidayati Fitri; Masna Yunita; Esti Royani; Kevin M. Rivera; Viorizza Suciani Putri (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2025)
There are several facets to the complicated problem of polygamy in Indonesia, including positive law, Islamic law, and societal factors. While Islam does provide a legal framework for polygamy and Law Number 1 of 1974 concerning Marriage does regulate it thoroughly, it might be challenging to put the idea of fairness as the primary criterion into practice. The issue that affects the legal protection of women and children stems from polygamy's injustice, which includes both material and non-material components, and from the lack of strong oversight of unregistered marriage practices. In order to better safeguard women and children involved in polygamy, this research will examine the degree to which legal standards are followed and how these standards are put into effect. Combining a socio-legal framework to comprehend its social application with a legal examination of Islamic and national legal norms, this research employs a normative descriptive technique with a qualitative approach. Findings reveal that unregistered weddings and other legal loopholes continue to be a big problem, even though laws have been enacted to restrict careless polygamy. Legal change, including the digitization of marriage registration, stricter polygamy permission processes, and the empowerment of women, are proposed remedies in this research. Another tactic for creating a flexible and responsive legal system is to combine local values with international norms like CEDAW. This study's findings will help shape Indonesia's marriage law policy in a more equitable and welcoming direction.